MHD Boundary Layer Flow of Casson Fluid Past an Inclined Plate in the Presence of Soret/Dufour Effects, Heat Source and First-order Chemical Reaction - Das, U. J. (Journal of Scientific Research, 2021)
The main objective of this study is to investigate the effects of the Casson fluid parameter on an incompressible, magnetohydrodynamic boundary layer flow of a Casson fluid past a moving porous inclined plate in the presence of heat source and first-order chemical reaction. The governing partial differential equations are converted into ordinary differential equations using similarity transformation and then are solved numerically, adopting bv4pc method. The effects of relevant parameters on the velocity, temperature and concentration profiles are analyzed graphically. Also, tabular form is used to present skin friction, heat transfer and mass transfer. This investigation reveals that the Casson fluid parameter enhances the fluid velocity, skin friction and Sherwood number, while the Nusselt number decreases.